Islamic law perspectives and social experiences on stigma toward disabled people in Indonesia - Billah, Muktashim; Gassing, Abdul Qadir; Bakry, Muammar; Kurniati, Kurniati; Haddade, Abdul Wahid; Syamsuddin, Darussalam; Ahmad, La Ode Ismail; Harakan, Ahmad (Frontiers in Sociology, 2025)
IntroductionStigmatization of disabled individuals remains a significant issue in Indonesia, particularly in Makassar, despite the existence of legal protections. This issue is further complicated by the intersection of religious and cultural norms, especially in Muslim-majority contexts. Islamic law (Maqāṣid al-Sharı̄'ah) provides a framework for dignity, intellect, and social justice, yet societal perceptions often contradict these principles. This study investigates how social stigma—manifested through harassment, insults, and negative labeling—aligns or conflicts with Islamic teachings on compassion and inclusion.MethodsA mixed-methods approach was employed, combining qualitative interviews with key informants and quantitative survey data from 400 respondents, sampled using the Taro Yamane formula. The study examines the prevalence of stigma against disabled people and explores the role of Islamic perspectives in shaping societal attitudes.ResultsFindings reveal that stigma against disabled individuals in Makassar is deeply embedded in social structures, often reinforcing their marginalization. While Islamic teachings promote inclusivity and protection of dignity, cultural misinterpretations and lack of awareness contribute to inconsistent application. The quantitative data indicate a strong correlation between negative labeling and social exclusion, while qualitative insights highlight the role of religious leaders and societal norms in shaping public perception.DiscussionThe study highlights Maqāṣid al-Sharı̄'ah as a potential framework to counter stigma and advocate for more inclusive policies. However, societal resistance and entrenched biases pose challenges to implementation. Addressing these issues requires enhanced public education, stronger legal enforcement, and community engagement to shift societal attitudes toward disability rights.ConclusionThis research contributes to the discourse on Islamic social justice and disability rights, emphasizing the need for a comprehensive approach to reducing stigma. Policy recommendations include involving disabled individuals in public decision-making, strengthening religious and legal discourse on inclusion, and promoting awareness campaigns to challenge societal prejudices. These efforts are essential to fostering a more equitable and inclusive society.